RELIGIOUS COURT IN INDONESIA: History and Prospect (JOURNAL OF INDONESIAN ISLAM, 2009)
Since the enactment of Law No. 7 in 1989, religious courts have gained an equal position, in terms of jurisdiction, to other courts in Indonesia, a status that took a considerable time to realize. This article discusses the historical development of religious courts in Indonesia from the early period of Islam in the country to the post-independence period. It particularly highlights internal and external factors which underpin the development of religious courts. Further, this paper examines the development of religious courts under the auspices of the Supreme Court. In the early period of Islam in Indonesia, there was no explicit dichotomy between Islamic and public courts. Religious courts had sole power in the judiciary. During the colonial period, however, the Dutch and Japanese limited the authority of religious courts. After Indonesian independence, the status and authority of religious courts did not change much until the implementation of the Law in 1989.